Occupational Neurobrucellosis Mimicking a Brain Tumor: A Case Report and Review of the Literature - Hussein Algahtani; Bader Shirah; Dina Abdulghani; Roiya Farhan; Raghad Algahtani (Case Reports in Infectious Diseases)
Brucellosis is a zoonotic bacterial infection which is transmitted to humans from infected animals and is endemic in many parts of the world including Saudi Arabia. In this article, we report a case of occupational neurobrucellosis that presented with a space-occupying lesion mimicking a brain tumor. We stress on the importance of obtaining detailed social history including occupation to reach the diagnosis in several conditions including brucellosis. We also stress on taking universal precautions when handling any specimens. It may be advisable that manipulation of all unknown specimens arriving at the laboratory should occur in biological safety cabinet until a highly infectious organism is ruled out. Neurobrucellosis should be included in the differential diagnosis in patients presenting with solitary mass lesion mimicking brain tumor especially in endemic areas or high occupational risk group.